Development of the composition and technology of an orodispersible film with melatonin and magnesium citrate - Butkevych , Tetiana; Polova , Zhanna; Savchenko, Sofia (The Ukrainian Scientific Medical Youth Journal, 2023)
sleep disorders are one of the most common problems among the population today. Numerous scientific publications indicate the effectiveness and safety of melatonin and magnesium use as active ingredients in medicinal products in older adults with sleep disorders. The technological development of an oromucosal preparation – an orodispersible film with melatonin and magnesium citrate is relevant in view of the possibility of increasing the patients’ compliance, those who find it difficult to take oral dosage forms (tablets, capsules) due to possible hand tremors and swallowing disorders. The aim of the study was to develop orodispersible films’ with melatonin and magnesium citrate formulations of various compositions, to conduct a comparative study of their technological parameters in order to select the optimal composition of excipients. The orodispersible films were made by solvent casting method. Melatonin and magnesium citrate were combined with representatives of 6 excipients groups (hydrophilic polymers: agar-agar, xanthan gum, sodium alginate, carboxymethyl cellulose, hydroxypropyl methyl cellulose E3, plasticisers: macrogol 400, glycerol and propylene glycol, saliva stimulants: ascorbic, lactic and citric acids, disintegrant: sodium croscarmellose, sweeteners: sorbitol, erythrol and sucralose, solvent: purified water). Formulations of 9 experimental samples were formed. The prepared solutions were filled into appropriate Petri dishes and dried in several steps. The technological parameters of the dried and cut into 2×3.5 cm orodispersible films were determined: appearance and surface characteristics, average weight and it`s uniformity, area and film thickness, folding endurance, in-vitro disintegration time, and physico-chemical parameter: surface pH value. Formulation No. 5, when dried at 60 ⁰C for 3 hours and 60 ⁰C for 3 hours / 40 ⁰C for 2 hours, and left for congealing for 24 hours at 25±2 ⁰C, formed dry to the touch, durable elastic transparent orodispersible film with very close stable values of parameters (average weight 0.40±0.01 g, area 7 cm2, thickness 0.32±0.05 mm and 0.32±0.03 mm, respectively, folding endurance ˃ 300, pH 6.70±0.04 and 6.74±0.05, respectively, in-vitro disintegration time 32.00±0.67 s and 31.00±0.67 s, respectively). The technology is suitable and it is possible to obtain dry to the touch, durable, elastic transparent films with satisfactory values of the studied parameters under the specified drying conditions.